Microcephaly in Neurometabolic Diseases - Wiktoria Kempińska; Karolina Korta; Magdalena Marchaj; Justyna Paprocka (MDPI AG, 2022)
Neurometabolic disorders are an important group of diseases that mostly occur in neonates and infants. They are mainly due to the lack or dysfunction of an enzyme or cofactors necessary for a specific biochemical reaction, which leads to a deficiency of essential metabolites in the brain. This, in turn, can cause certain neurometabolic diseases. Disruption of metabolic pathways, and the inhibition at earlier stages, may lead to the storage of reaction intermediates, which are often toxic to the developing brain. Symptoms are caused by the progressive deterioration of mental, motor, and perceptual functions. The authors review the diseases with microcephaly, which may be one of the most visible signs of neurometabolic disorders.